A terminologia relativa à hanseníase Terminology related to hansen's disease - Paula Araujo Opromolla; Antonio Carlos Ceribelli Martelli (Sociedade Brasileira de Dermatologia, 2005)
A padronização internacional de doenças é um processo complexo que necessita de uma equipe especializada. Esta comunicação visa a esclarecer e sugerir correções de um provável equívoco na tradução, para o português da CID-10, do código A30, no qual os termos "borderline" e "dimorfo" são utilizados como subcategorias distintas e não como sinônimos, assim como substituir a designação "lepromatosa" por "virchoviana" pois, no Brasil, o vocábulo "lepra" foi abolido dos textos oficiais, por uma lei federal em 1995. The international standardization of diseases is a complex process that requires a specialized team. The aim of this work is to clarify and suggest some corrections for a probable misunderstanding during the translation of ICD-10 code A30 into Portuguese, in which the terms borderline and dimorfo (dimorphous) are used as different subcategories and not as synonyms; moreover, the designation lepromatosa (lepromatous) should be replaced by virchoviana (virchowian) considering that in Brazil, the word lepra (leprosy) was abolished from official texts by a Federal Act in 1995.